Questions about the early history of the Slavs in the light of župa Bled - Pleterski, Andrej (Arheološki vestnik, 2013)
Although today Slavs inhabit the majority of Europe, their history is poorly known because they came relatively late in the light of written sources. This paper presents the results of interdisciplinary research of the micro-region of Bled, which reveals the life of the Slavs that is not mentioned in written sources. The image of the administrative, economic, political, identity unit is displayed, which can be identified as Slavic župa, which were basic building blocks of Slavic society. The author analyses their significance for the understanding of the ancient Slavs.